Particle-density segregation of rock–ice avalanche - Zhiping Sun; Shentian Li; Jinkun Dong; Zhibo Dong; Siyou Xiao (AIP Advances)
Rock-ice avalanches occurring in cold high-mountains have super mobility and enormous destructive potential. They consist mainly of ice and gravel with different physical properties, particularly density, leading to segregation and impacting the flow characteristics. However, how key factors affect segregation is still poorly understood. A series of simulations based on the discrete element method were conducted to quantify the effect of channel slope, ice content, and initial arrangement of ice-gravel on the segregation of rock-ice granular flow. Results show that a smaller slope and lower ice content promote density segregation of the rock-ice granular flow, allowing segregation to proceed more thoroughly, but interestingly, the initial arrangement of ice-gravel does not affect its final segregation state. This work provides insights into the effect of internal and external factors on the density difference-driven segregation for multi-component mixtures typified by rock-ice granular flow.